Muscle mass and vertical jump ability in young female handball players - Perez-Gomez, J.; Vicente-Rodriguez, G.; Ara Royo, I.; Calbet, J. A. L.; Dorado, C. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
prepubertal children, despite a similar lower limb muscle mass (Vicente-Rodriguez et al. 2003). Puberty entails marked changes in girls body composition which by itself may affect exercise performance. So the aim of this study was to find out if the participation in handball is associated or not with increased lower limb muscle mass and how the latter could influence jumping performance in young postpuberal female handball players. Methods Forty-seven postpuberal girls (14.4 ± 0.4 yr, mean ± SEM) were assigned to the handball group (HG) (N = 21) that trained regularly ten hours per week or control group (CG) (N = 26) who did not participate in regular training. Subjects performed maximal countermovement (CMJ) and squat (SJ) jumps on a force plate; height jump (Hj), positive mechanical impulse (IMP), maximal vertical velocity (Vmax), mean (Pm) and maximal power output (Pmax), were analysed. The percentage of body fat (%BF), total lean mass (LT), lean mean mass of the lower limbs (LL) and lean mean mass of the arms (LA) were assessed by dual-energy X-ray absorptiometry (DXA). Differences between groups were established using Student`s unpaired t test (p<0.05). Results Anthropometrics and body composition were similar in both groups. No significant differences in vertical jump performance were observed between HG and CG (table 1). The IMP and Pmax have the best correlations with LA, LL and LT. (table 2). Conclusion The practice of handball ten hours per week has not effect in jumping performance in postpuberal girls. In addition, jumping performance variables appear to depend on lower limb muscle mass.